Photocatalytic degradation of xanthate in flotation plant tailings by TiO2/graphene nanocomposites - Jiang, Man; Zhang, Minghui; Wang, Longzhen; Fei, Yawen; Wang, Shuo; Nunez-Delgado, Avelino; Bokhari, Awais (Elsevier Science Sa, 2022)
This study has invented a novel composite photocatalytic material of TiO2/graphene (TiO2/G) via the hydro thermal method. The prepared TiO2/graphene (TiO2/G) composite catalysts were investigated in detail using various characterisation experiments. The characterisation experiments indicated that the TiO2/graphene (TiO2/ G) nanocomposites were successfully prepared. It can be observed that the TiO2 nanoparticles were observed uniformly distributing on the graphene oxide (GO) and the prepared TiO2/graphene (TiO2/G) nanocomposites possess huge specific surface area, small pore size, and low electron-hole pair complexation rate to degrade the pollutants. For the first time, TiO2/G is used as a photocatalytic material to treat mineral processing wastewater. Compared to GO and TiO2, under simulated light irradiation, the photodegradation efficiency of 18% TiO2/G samples reached 97.03% after 100 min. By successfully anchoring TiO2 on GO, the photoresponse range of TiO2/G was broadened (from 200-380 nm to 200-800 nm). The activity was also further improved (after 100 min of simulated light, the photocatalytic efficiency of pure TiO2 was only 17.88%, and the photocatalytic efficiency of 18% TiO2/G was 5.43 times higher than that of pure TiO2). This work advances the development of a potential photo-, photoelectro-systems for the treatment of real mineral processing wastewater.
Keywords: TiO2; Graphene oxide; Photodegradation; Mineral processing; Wastewater treatment